MENINGKATKAN KARAKTER PEDULI LINGKUNGAN PADA USIA DINI MELALUI SOSIALISASI SAMPAH DAN PENGELOLAAN SAMPAH 3R (REDUCE, RECYCLE DAN REUSE) DI SDN 022 PALARAN KALIMANTAN TIMUR - Deandlles Christover; Rusli Rusli; Amirullah Amirullah (Jurnal Pengabdian Masyarakat Borneo, 2023)
In 2021, Indonesia is ranked as the fifth largest plastic waste producing country in the world after the Philippines, India, Malaysia and China. Garbage that accumulates without proper management can cause problems, such as disease and produce hazardous chemicals. Garbage that piles up in ditches and rivers also causes flooding which is a routine disaster in the country. Recognizing the types of waste from an early age by disposing of waste according to its type is a simple habit that will have a big impact on the environment and this attitude really needs to be formed so that it becomes a good habit for future generations. The purpose of this service activity is to foster the character of caring for the environment for children at an early age. The method of implementing the activity is in the form of observation to look for problems at SDN 022 PALARAN and carry out waste socialization and waste management activities using the 3R method (reduce, recycle, and reuse).